TEACHER`S PEDAGOGICAL COMPETENCE IN TEACHING AND THEIR PROFESSIONAL DEVELOPMENT STRATEGY - Aulia Mufida Izzatul Mahfiana; Nizam Ahsani (Journal of Social and Economics Research, 2023)
This study tried to portray EFL teachers’ pedagogical competence and their development strategy. It aimed to analyze EFL teachers’ pedagogical competence in an Islamic boarding school in East Java and investigate their development strategy for developing their pedagogical competence. This research used descriptive qualitative. The data were collected through semi-structured interview, open-ended questionnaires and observation. The findings showed that based on the respondents’ questionnaire over teachers’ competence stipulated by The Decree of the Minister of National Education No.16, 2007 on the Standards of Academic Qualifications and Competencies of Teachers (SAQ-CT), the teachers’ competencies were categorized ‘good’, as well as their professional development to improve their pedagogical.